KONSEP PEMBATASAN HAK MILIK (TAHDID AL-MILKIYYAH) DAN PENGAMBILALIHAN HAK MILIK ATAS TANAH (AL-TAâMIM) MENURUT SYARIâAT ISLAM - Kusasy, M. Arsyad (Al-Mawarid Jurnal Hukum Islam, 2003)
The writer of the article discourses the concept of âtahdid al-milkiyahâ ( the limitation of ownership ) and al-taâmim ( the nationalization). The realization of both tahdid almilkiyah and al-taâmim can be justified according to the decisions of Islamic Syariâat. And the public interest (maslahah ammah) principle denotes the fundament of the realization of two concepts above-mentioned. The most important in this sense is the application of tahdid al-milkiyah will give the utility for the needs of community, society, and the state. So will the concept of al-taâmim, if a state in emergency cunducted the nationalization of wealth from its owner because of the necessity of the public, but the government should pay fine. If the steps of the realization of both concepts afore-mentioned tahdid al-milkiyah and al-taâmim should realize wisely will applicable well.